THE KINDS AND THE MEANING OF TEMBANG MACAPAT FOR JAVANESE PEOPLE - Natalia Desy Endriana (Conscientia, 2020)
The writer wants to study tembang Macapat. The objectives of this article are to understand more about tembang Macapat and to know the kinds and the meaning of tembang Macapat. In this graduating article, the writer use two methods they are library research and interview. In this article the writer found that there are eleven kinds of tembang Macapat :Maskumambang, Mijil, Sinom. Asmaradhana, Kinanthi, Dhandhanggula, Pangkur, Durma, Pucung, Gambuh and Megatruh.The meanings can be classified into these themes: about kingdom, traditional dance and love.